Catalytic Decarboxylative C−N Formation to Generate Alkyl, Alkenyl, and Aryl Amines. Issue 4 (27th November 2020) - Zhang, Yipin; Ge, Xia; Lu, Hongjian; Li, Guigen
Abstract: Transition‐metal‐catalyzed sp 2 C−N bond formation is a reliable method for the synthesis of aryl amines. Catalytic sp 3 C−N formation reactions have been reported occasionally, and methods that can realize both sp 2 and sp 3 C−N formation are relatively unexplored. Herein, we address this challenge with a method of catalytic decarboxylative C−N formation that proceeds through a cascade carboxylic acid activation, acyl azide formation, Curtius rearrangement and nucleophilic addition reaction. The reaction uses naturally abundant organic carboxylic acids as carbon sources, readily prepared azidoformates as the nitrogen sources, and 4‐dimethylaminopyridine (DMAP) and Cu(OAc)2 as catalysts with as low as 0.1 mol % loading, providing protected alkyl, alkenyl and aryl amines in high yields with gaseous N2 and CO2 as the only byproducts. Examples are demonstrated of the late‐stage functionalization of natural products and drug molecules, stereospecific synthesis of useful α‐chiral alkyl amines, and rapid construction of different ureas and primary amines. Abstract : A decarboxylative C−N formation between organic carboxylic acids and azidoformates was achieved in the presence of 4‐dimethylaminopyridine (DMAP) and Cu(OAc)2 as catalysts. This reaction provides various protected amines with gaseous N2 and CO2 as the only byproducts.